The circles of life (3) Half the world hungry: been there done that - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1999)
The circles of life (3) Half the world hungry: been there done thatDo not be shocked. The worst is still to come. The full expression is 'Been there, done that, got the T-shirt' and it is used by people with a desire to be complacent about their...